2010
DOI: 10.1016/j.ijdevneu.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of maternal serotonin transporter genotype and prenatal stress in modulating offspring social interaction in mice

Abstract: Several studies suggest that prenatal stress is a possible risk factor in the development of autism spectrum disorders. However, many children exposed to stress prenatally are born healthy and develop typically, suggesting that other factors must contribute to autism. Genes that contribute to stress reactivity may, therefore, exacerbate prenatal stress-mediated behavioral changes in the adult offspring. One candidate gene linked to increased stress reactivity encodes the serotonin transporter. Specifically, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 53 publications
4
48
0
Order By: Relevance
“…On postnatal day 25, offspring were assessed to ensure that neuromuscular, sensory, and other functional systems were intact, as described previously (60,61). Olfaction was tested by placing a small piece of food (cookie crumbs, 20 mg) under the bedding in a clean mouse cage that was visually, but not physically, divided into nine quadrants.…”
Section: Methodsmentioning
confidence: 99%
“…On postnatal day 25, offspring were assessed to ensure that neuromuscular, sensory, and other functional systems were intact, as described previously (60,61). Olfaction was tested by placing a small piece of food (cookie crumbs, 20 mg) under the bedding in a clean mouse cage that was visually, but not physically, divided into nine quadrants.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in line with the repetitive behaviors displayed by ASD patients (Pierce and Courchesne, 2001), 5-HTT knockout mice displayed higher frequencies of self-grooming than their wild-type littermates (Kalueff et al, 2010; Lewejohann et al, 2010). In the domain of communication, which is affected in ASD, it has been reported that wild-type mice show more ultrasonic vocalizations (USVs) within the 20–40 kHz range than prenatally stressed animals of both 5-HTT +/+ and 5-HTT +/− genotypes, as well as non-stressed 5-HTT +/− animals (Jones et al, 2010). Furthermore, 5-HTT −/− rats show reduced prepulse inhibition (Page et al, 2009), implying the sensorimotor integration is impaired in these animals, such that they are unable to efficiently select sensory information from the external world.…”
Section: -Htt Gene Variance In Humans and Rodentsmentioning
confidence: 99%
“…132 The risk of ASD associated with prenatal psychosocial stress seems to be linked to maternal genetic susceptibility to greater stress reactivity. 133 Furthermore, in a rodent model, prenatal stress exposure in offspring of genetically stress susceptible mothers has been shown to result in aberrant social behavior, 134 which was also associated with delayed migration of GABAergic neurons during development. 135 Maternal exposure to stress before pregnancy and even early life stress is associated with increased risk for development of ASD in subsequent pregnancies according to recent findings in data from the Nurses' Health Study.…”
Section: Environmental Exposures As a Potential Biologically Salient mentioning
confidence: 99%
“…For example, patients who do not have a known ASD-associated GABAergic mutation but who have a similar level of GABAergic activity, as potentially assessed by magnetic resonance spectroscopy or electroencephalography markers, 57,63 as patients with these mutations might also be expected to respond similarly to drugs developed based on the GABAergic mutation-based ASD mouse model. Furthermore, animal models have also been developed for environmental factors, including prenatal stress models, 134 maternal immune models, 125,126,177 and drug effect models. 148 Therefore, these principles can also be extended to incorporate environmental cause/risk factors onto the cause/biomarker map of developing neural systems.…”
Section: Phenotyping Biomarkers and Treatment Trialsmentioning
confidence: 99%